Evidence for myocardial CT perfusion imaging in the diagnosis of hemodynamically significant coronary artery disease - Sun, Zhonghua (2015)
This editorial discusses a recent paper published in the August issue of Radiology about the diagnostic value of myocardial computer tomography (CT) perfusion imaging in the detection of hemodynamically significant coronary stenosis when compared to single-photon emission CT (SPECT) imaging based on a secondary analysis of CORE320 study. Three aspects including high diagnostic sensitivity of CT perfusion imaging, moderate specificity of SPECT imaging and lack of use of attenuation correction in SPECT imaging have been discussed with reference to the current literature, and some suggestions have been highlighted for future studies to improve the diagnostic performance of CT perfusion and SPECT imaging in the diagnostic evaluation of coronary artery disease.